Zależność pomiędzy stadium rozwoju małego i średniego przedsiębiorstwa a jego strukturą kapitałową - ujęcie teoretyczne - Adamek, Jacek (The stage of entity development as the factor influencing capital structure of a small and medium enterprise, 2007)
The objective of the hereby paper becomes an attempt to define interdependencies which occur between the capital structure of a small and medium enterprise and the stage of its development. The underlying reason for performed research (consisting in professional literature analysis) became the standpoint that changes in company’s development refering to changes in its access to financing sources as well as changes in its capital structure. These interrelations could be explained on the basis of the life-cycle model, which became the subject matter of the conducted studies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1186, s. 164-170